Sendo A=a+b-c, B=a-b-c e C=a-b+c, determine:
a)A-B
b)C - A
pfvr alguem pode me explicar como resolver??
Respostas
respondido por:
1
Resposta:
Explicação passo-a-passo:
Temos
A = a + b - c
B = a - b - c
C = a - b + c
Assim,
a)
A - B = a + b - c - (a - b - c)
A - B = a + b - c - a + b + c
A - B = b + b
A - B = 2b
b)
C - A = a - b + c - (a + b - c)
C - A = a - b + c - a - b + c
C - A = c + c
C - A = 2c
amandamachado12359:
bgdaaaa
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás